2014
DOI: 10.1111/joor.12234
|View full text |Cite
|
Sign up to set email alerts
|

Upper canine inclination influences the aesthetics of a smile

Abstract: This current study investigated which angle of canine inclination (angle between canine tooth axis (CA-line) and the line between the lateral canthus and the ipsilateral labial angle (EM-line)) is perceived to be most attractive in a smile. The second objective was to determine whether laymen and dental experts share the same opinion. A Q-sort assessment was performed with 48 posed smile photographs to obtain two models of neutral facial attractiveness. Two sets of images (1 male model set, 1 female model set)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In a study conducted by Bothung et al the effect of inclination of upper maxillary canines has been evaluated [6]. Hideki Ioi et al demonstrated the effect of vertical positions of anterior teeth on smile esthetics in South Korea and Japan [7].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Bothung et al the effect of inclination of upper maxillary canines has been evaluated [6]. Hideki Ioi et al demonstrated the effect of vertical positions of anterior teeth on smile esthetics in South Korea and Japan [7].…”
Section: Introductionmentioning
confidence: 99%
“…Human canines are an integral part of smiling and are important for the overall esthetics of a smile [ 1 , 2 ]. Esthetical analyses that consider attractiveness and focus on human canine morphology are rarely found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The maxillary and mandibular canines are anterior teeth that are placed at the corners of the mouth, and their positions and forms of these teeth along with the canine eminence play a vital role in aesthetics and face value. The inclination of the upper canine also influences the aesthetics specially a smile [9]. Hence, any change in its position or early loss may not only unduly affect the general appearance but may also psychologically impact an individual.…”
Section: Introductionmentioning
confidence: 99%